Battery packaging material, method for producing the same, and battery
By presenting a specific amount of slip agent on the side surface of the substrate layer of the battery packaging material and adopting a stacked structure, the problems of cracks and pinholes during the molding process are solved, and the continuous productivity and moldability of the battery are improved.
Patent Information
- Application Number
- CN202111454637.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-04-12
- Filing Date
- 2017-04-12
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2037-04-12
AI Technical Summary
The existing packaging materials for batteries are prone to cracks and pinhole problems during the molding process, and the adhesion of the slip agent to the mold leads to poor sealing, affecting the continuous productivity of the battery.
A laminated body including a base material layer, a barrier layer and a hot-weld resin layer is used, and a slip agent is present at least on the surface of the base material layer side, and the slip agent is controlled to be 15 mg/m2 or more and 60 mg/m2 or less to improve moldability and continuous productivity.
Excellent performance of high moldability and continuous battery productivity is achieved, and the problems of slip agent accumulation and poor bonding are avoided.
Smart Images

Figure CN114156573B_ABST
Abstract
Description
[0001] This case is filed on April 12, 2017 、Application number is 201780023320.0 (PCT / JP2017 / 015041) , divisional application for invention titled "Battery packaging material, manufacturing method thereof and battery". Technical Field
[0002] The present invention relates to a battery packaging material, a method for producing the same, and a battery. Background Art
[0003] In the past, various types of batteries have been developed, and in all batteries, packaging materials have become an indispensable component in order to encapsulate battery elements such as electrodes or electrolytes. In the past, metal packaging materials were mostly used as battery packaging bodies, but in recent years, with the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., batteries are required to have various shapes, and to be thinner and lighter. However, in the metal battery packaging materials that have been mostly used in the past, it is difficult to keep up with the diversification of shapes, and there are also disadvantages that lightweighting is limited.
[0004] Therefore, as a battery packaging material that can be easily processed into various shapes and can be thinned and lightened, a film-like laminated body having a base layer / adhesive layer / barrier layer / thermo-fusible resin layer laminated in this order has been proposed (for example, see Patent Document 1). Such a film-like battery packaging material is formed so that the battery element can be encapsulated by placing the thermo-fusible resin layers facing each other and heat-sealing the peripheral portions.
[0005] In battery packaging materials, when enclosing battery elements, a mold is used to form a space for storing the battery elements. During this molding, there is a problem that cracks and pinholes are easily generated in the barrier layer at the flange part of the mold due to the stretching of the battery packaging material. In order to solve such a problem, there is a known method of improving the sliding property of the battery packaging material by applying a lubricant on the surface of the heat-fusible resin layer of the battery packaging material, or by adding a lubricant to the heat-fusible resin layer so that it seeps out on the surface. By adopting such a method, the battery packaging material can be easily introduced into the mold during molding, and cracks and pinholes in the battery packaging material can be suppressed.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-287971 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] If the amount of lubricant present on the surface of the heat-fusible resin layer of the battery packaging material is too much, there is a problem that the lubricant adheres to the mold, forms lumps and contaminates the mold. When other battery packaging materials are molded in the case of a contaminated mold, the lumps of lubricant attached to the mold adhere to the surface of the battery packaging material, and in this state are provided for heat welding of the heat-fusible resin layer. In this way, when the heat-fusible resin layer is heat-fused, the melting of the part attached with the lubricant is uneven, so poor sealing occurs. In order to prevent this situation, it is necessary to increase the cleaning frequency for removing the lubricant attached to the mold, which has the problem of reducing the continuous productivity of the battery.
[0011] On the other hand, if the amount of the lubricant present on the surface of the battery packaging material is too small, the sliding property of the battery packaging material is reduced, which causes a problem in that the moldability of the battery packaging material is reduced.
[0012] Under such circumstances, a main object of the present invention is to provide a battery packaging material having high moldability and excellent continuous productivity of batteries.
[0013] Technical solutions for solving technical problems
[0014] The inventors of the present invention have conducted intensive research to solve the above technical problems. As a result, they found that a laminated body having at least a substrate layer, a barrier layer and a heat-fusible resin layer in this order, a lubricant is present on at least the surface of the substrate layer side of the laminated body, and the total amount of lubricant on the surface of the substrate layer side of the laminated body and the amount of lubricant on the surface of the heat-fusible resin layer of the laminated body is 15 mg / m 2 Above, 60mg / m 2 The following battery packaging material has high moldability and is excellent in continuous battery productivity, and is suitable for battery production. The present invention has been completed through further research based on these findings.
[0015] That is, the present invention provides a battery packaging material and a battery in the following aspects.
[0016] Item 1. A battery packaging material comprising a laminate having at least a substrate layer, a barrier layer and a heat-fusible resin layer in this order,
[0017] A lubricant is present at least on the surface of the laminate on the substrate layer side.
[0018] The total amount of lubricant on the surface of the substrate layer side of the laminate and the amount of lubricant on the surface of the thermally fusible resin layer of the laminate was 15 mg / m 2 Above, 60mg / m 2 the following.
[0019] Item 2. The battery packaging material according to Item 1, wherein the amount of lubricant present on the surface of the laminate on the substrate layer side is 3 mg / m 2 Above, 15mg / m 2 the following.
[0020] Item 3. The battery packaging material according to Item 1 or 2, wherein the amount of lubricant present on the surface of the thermally fusible resin layer of the laminate is 10 mg / m 2 Above, 50mg / m 2 the following.
[0021] Item 4. The battery packaging material according to any one of Items 1 to 3, wherein the base layer comprises at least one of a layer made of polyester and a layer made of polyamide.
[0022] Item 5. The battery packaging material according to any one of Items 1 to 4, further comprising a surface coating layer on the side of the substrate layer opposite to the barrier layer.
[0023] Item 6. The battery packaging material according to any one of Items 1 to 5, wherein the lubricant comprises an amide-based lubricant.
[0024] Item 7. The battery packaging material according to any one of Items 1 to 6, wherein the thermally fusible resin layer comprises a layer formed of a polyolefin.
[0025] Item 8. The battery packaging material according to any one of Items 1 to 7, comprising a base film layer on at least one surface of the barrier layer.
[0026] Item 9. The battery packaging material according to any one of Items 1 to 8, which is a packaging material for a secondary battery.
[0027] Item 10. A battery comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte housed in a packaging body formed of the battery packaging material according to any one of Items 1 to 9.
[0028] Item 11. A method for producing a battery packaging material, comprising the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in this order,
[0029] The lubricant is present at least on the surface of the substrate layer side of the laminate, and the total amount of the lubricant on the surface of the substrate layer side of the laminate and the lubricant on the surface of the thermally fusible resin layer of the laminate is set to 15 mg / m 2 Above, 60mg / m 2 the following.
[0030] Item 12. The method for producing a battery packaging material according to Item 11, further comprising the step of subjecting at least one surface of the base layer to a corona discharge treatment.
[0031] Effects of the Invention
[0032] According to the present invention, it is possible to provide a battery packaging material having high moldability and excellent in continuous productivity of batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0034] Figure 2 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0035] Figure 3 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0036] Figure 4 This is a schematic diagram showing an example of the cross-sectional structure of the battery packaging material of the present invention.
[0037] Figure 5 It is a schematic diagram showing the crystal grains and the second phase particles in the thickness direction of the aluminum alloy foil layer.
[0038] Explanation of symbols
[0039] 1 base material layer, 2 adhesive layer, 3 barrier layer, 4 heat-fusible resin layer, 5 adhesive layer, 6 surface covering layer, 10 battery packaging material. DETAILED DESCRIPTION
[0040] The battery packaging material of the present invention is characterized in that it comprises a laminate having at least a substrate layer, a barrier layer and a heat-fusible resin layer in this order, a lubricant is present at least on the surface of the substrate layer side of the laminate, and the total amount of the lubricant on the surface of the substrate layer side of the laminate and the lubricant on the surface of the heat-fusible resin layer of the laminate is 15 mg / m 2 Above, 60mg / m 2 the following.
[0041] Hereinafter, the battery packaging material of the present invention will be described in detail.
[0042] 1. Laminated structure of battery packaging materials
[0043] like Figure 1As shown in the figure, the battery packaging material of the present invention includes a laminate having at least a base layer 1, a barrier layer 3, and a heat-fusible resin layer 4 in this order. In the battery packaging material of the present invention, the base layer 1 is the outermost layer, and the heat-fusible resin layer 4 is the innermost layer. That is, when assembling a battery, the heat-fusible resin layers 4 located at the periphery of the battery element are heat-fused to each other to seal the battery element, thereby encapsulating the battery element.
[0044] like Figure 2 As shown in FIG. 1 , in the battery packaging material 10 of the present invention, an adhesive layer 2 may be provided between the base layer 1 and the barrier layer 3 as required for the purpose of improving the adhesion between them. Figure 3 As shown in FIG. 1 , in the battery packaging material 10 of the present invention, an adhesive layer 5 may be provided between the barrier layer 3 and the heat-fusible resin layer 4 as required for the purpose of improving the adhesiveness thereof. Figure 4 As shown, a surface coating layer 6 may be formed on the surface on the base material layer 1 side.
[0045] The thickness of the laminate constituting the battery packaging material 10 of the present invention is not particularly limited. From the viewpoint of reducing the thickness of the battery packaging material to increase the energy density of the battery and forming a battery packaging material with excellent moldability, for example, it can be about 150 μm or less, preferably about 120 μm or less, more preferably about 50 μm to 100 μm, and further preferably about 50 μm to 80 μm.
[0046] In the battery packaging material 10 of the present invention, a lubricant is present on the surface of the base layer 1, and the total amount of the lubricant on the surface of the base layer side of the laminate constituting the battery packaging material 10 and the lubricant on the surface of the heat-fusible resin layer of the laminate is 15 mg / m 2 Above, 60mg / m 2 The battery packaging material of the present invention has high moldability and excellent continuous production of batteries by having a lubricant on the surface of the substrate layer 1 and by making the amount of lubricant on the surface of the battery packaging material 10 within this specific range. The details of this mechanism are not intended to be interpreted restrictively, but it can be considered as follows. That is, it can be considered that the lubricant is present on the surface of the substrate layer 1 and the total amount of the lubricant is 15 mg / m 2 When the total amount of lubricant is 60 mg / m3, the sliding property between the mold and the battery packaging material is improved, and the battery packaging material can be easily pulled in during deep drawing with a male die, so deep drawing can be performed, and pinholes and breaks are not likely to occur. On the other hand, it can be considered that by setting the total amount of lubricant to 60 mg / m3, the battery packaging material can be easily pulled in during deep drawing with a male die. 2As a result, the lubricant is effectively suppressed from accumulating on the mold used for molding during the continuous production of batteries, and the attached lubricant is unlikely to be re-transferred to the battery packaging material, making it easy to avoid poor adhesion during heat sealing.
[0047] The total amount of the above lubricant is set to 15 mg / m 2 Above, 60mg / m 2 The following range of methods can be listed: a method of applying a lubricant on the surface of the substrate layer 1 side and the thermally fusible resin layer 4 side; a method of adding a lubricant to the resin constituting the layer on the substrate layer 1 side (for example, the substrate layer 1 or the surface coating layer 6) and the thermally fusible resin layer 4 and heating the layer to allow the lubricant to seep out of the surface.
[0048] From the viewpoint of forming a battery packaging material having further improved moldability and excellent continuous productivity of batteries, the lower limit of the total amount of lubricant on the surface of the substrate layer side of the laminate and the lubricant on the surface of the heat-fusible resin layer of the laminate is preferably 20 mg / m 2 Above, more preferably more than 40 mg / m 2 The upper limit is preferably 50 mg / m 2 In addition, as a preferred range of the total amount of the lubricant, 20 mg / m 2 Above 50 mg / m 2 Below, more than 40mg / m 2 and 50 mg / m 2 The following. In addition, the types of lubricants present on the surface of the laminate can be listed as lubricants exemplified in the base material layer 1 described later. In addition, as a method for measuring the amount of lubricant on the surface of the laminate, a predetermined area of the surface of the laminate is rinsed with a solvent, and the amount of lubricant contained in the obtained washing liquid (solvent) is quantitatively measured using a gas chromatography mass spectrometer (GC-MS) to obtain a value.
[0049] The amount of lubricant passing through the surface of the laminate on the substrate layer side was 3 mg / m 2 Above 15 mg / m 2 and the total amount of lubricant on the surface of the substrate layer side of the laminate and the amount of lubricant on the surface of the thermally fusible resin layer of the laminate exceeds 40 mg / m 2 , preferably more than 40 mg / m 2 and 50 mg / m 2 As a result, the moldability of the battery packaging material and the continuous productivity of the battery can be improved, and the printing properties on the surface of the base material layer 1 can be improved.
[0050] 2. Forming the layers of battery packaging materials
[0051] [Base material layer 1]
[0052] In the battery packaging material 10 of the present invention, the substrate layer 1 is a layer located on the outermost side. There are no particular restrictions on the raw materials forming the substrate layer 1 as long as they have insulating properties. As raw materials forming the substrate layer 1, for example, polyester, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, polycarbonate, and mixtures and copolymers thereof can be cited. Among these, it is preferred that the substrate layer 1 has at least one layer formed of polyester and a layer formed of polyamide.
[0053] Specific examples of the polyester include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolyesters containing ethylene terephthalate as a main repeating unit, and copolyesters containing butylene terephthalate as a main repeating unit. In addition, as copolyesters with ethylene terephthalate as the main body of repeating units, specifically, copolymer polyesters in which ethylene terephthalate is polymerized with ethylene isophthalate as the main body of repeating units (hereinafter referred to as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium isophthalate sulfonate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-diphthalate), polyethylene (terephthalate / sebacic acid ester), etc. can be listed. In addition, as the copolyester with butylene terephthalate as the main body of the repeating unit, specifically, there can be listed copolymer polyesters in which butylene terephthalate is polymerized with butylene isophthalate as the main body of the repeating unit (hereinafter referred to as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters can be used alone or in combination of two or more. Polyesters have advantages such as excellent resistance to electrolytes and are not prone to whitening due to the adhesion of electrolytes, and are suitable for use as raw materials for forming the substrate layer 1.
[0054] In addition, specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid; and aromatic polyamides such as poly(m-xylylene adipamide) (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); and polyamides obtained by copolymerizing a lactam component and an isocyanate component such as 4,4′-diphenylmethane-diisocyanate; polyester amide copolymers and polyether ester amide copolymers which are copolymers of a copolymerized polyamide with a polyester or a polyalkylene ether glycol; and copolymers thereof. These polyamides may be used alone or in combination of two or more. The stretched polyamide film has excellent stretchability and can prevent the occurrence of whitening due to resin cracking of the base layer 1 during molding, and is suitable as a raw material for forming the base layer 1.
[0055] The base layer 1 may be formed of a uniaxially or biaxially stretched resin film, or may be formed of an unstretched resin film. Among them, a uniaxially or biaxially stretched resin film, especially a biaxially stretched resin film, has improved heat resistance by oriented crystallization, and is therefore suitable for use as the base layer 1. In addition, the above-mentioned raw materials may be applied on the barrier layer 3 to form the base layer 1.
[0056] Among these, as the resin film forming the base material layer 1, preferably nylon and polyester are used, and more preferably biaxially stretched nylon and biaxially stretched polyester are used.
[0057] For the substrate layer 1, in order to improve the pinhole resistance and the insulation when the battery packaging body is made, at least one of the resin film and the coating of different raw materials can also be laminated (multilayer structure). Specifically, a multilayer structure obtained by laminating a polyester film and a nylon film, a multilayer structure obtained by laminating multiple layers of a nylon film, and a multilayer structure obtained by laminating multiple layers of a polyester film can be listed. In the case where the substrate layer 1 is a multilayer structure, a laminate of a biaxially stretched nylon film and a biaxially stretched polyester film, a laminate obtained by laminating multiple layers of a biaxially stretched nylon film, and a laminate obtained by laminating multiple layers of a biaxially stretched polyester film are preferably used. For example, when the substrate layer 1 is formed of two layers of resin films, it is preferably formed into a structure of laminating polyester resin and polyester resin, a structure of laminating polyamide resin and polyamide resin, or a structure of laminating polyester resin and polyamide resin, and more preferably formed into a structure of laminating polyethylene terephthalate and polyethylene terephthalate, a structure of laminating nylon and nylon, or a structure of laminating polyethylene terephthalate and nylon. In addition, since biaxially stretched polyester is not easily discolored when an electrolyte solution adheres to the surface, for example, when the substrate layer 1 is a multilayer structure of a laminate of a biaxially stretched nylon film and a biaxially stretched polyester film, it is preferred that the substrate layer 1 is a laminate having biaxially stretched nylon and biaxially stretched polyester in this order from the barrier layer 3 side. When the substrate layer 1 is a multilayer structure, the thickness of each layer is preferably about 2 μm or more and 25 μm or less.
[0058] When the substrate layer 1 is set as a multilayer structure, each resin film can be bonded by an adhesive, or it can be directly laminated without an adhesive. When not bonded by an adhesive, for example, methods of bonding in a hot melt state such as coextrusion, sandwich lamination, and hot lamination can be cited. In addition, when bonded by an adhesive, the adhesive used can be a two-liquid curing adhesive, or it can also be a one-liquid curing adhesive. In addition, there is no particular restriction on the bonding mechanism of the adhesive, and it can be any of a chemical reaction type, a solvent evaporation type, a hot melt type, a hot pressing type, an electron beam curing type, an ultraviolet curing type, etc. As a specific example of an adhesive, an adhesive similar to the adhesive illustrated in the adhesive layer 2 can be cited. In addition, about the thickness of the adhesive, it can also be the same as the adhesive layer 2.
[0059] The amount of lubricant present on the surface of the substrate layer 1 is not particularly limited as long as the above-mentioned total amount is satisfied. From the viewpoint of forming a battery packaging material having further improved moldability and excellent continuous productivity of the battery, 3 mg / m 2 Above, more preferably 4 mg / m 2 Above and 15 mg / m 2 The following is a more preferred example: 5 mg / m 2 Above 14 mg / m 2By setting the amount of lubricant present on the surface of the substrate layer 1 to such a value, the printing characteristics on the surface of the substrate layer 1 can be improved. The method for measuring the amount of lubricant present on the surface of the substrate layer 1 is the same as the method for measuring the amount of lubricant present on the surface of the laminated body described above.
[0060] Methods for setting the amount of lubricant on the surface of the substrate layer 1 to the above amount include: applying a lubricant on the surface of the substrate layer 1; and adding a lubricant to the resin constituting the substrate layer 1 and heating the resin to allow the lubricant to seep out of the surface.
[0061] There is no particular limitation on the type of lubricant, but preferably an amide lubricant is listed. As specific examples of amide lubricants, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethyl amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, etc. can be listed. As specific examples of saturated fatty acid amides, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, etc. can be listed. As specific examples of unsaturated fatty acid amides, oleic acid amide, erucic acid amide, etc. can be listed. As specific examples of substituted amides, N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, etc. can be listed. In addition, as specific examples of hydroxymethyl amides, hydroxymethyl stearic acid amide, etc. can be listed. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipamide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of the aromatic bisamides include meta-xylylene bisstearic acid amide, meta-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more.
[0062] The molecular weight of the lubricant is preferably about 100 to 1000. The molecular weight of the lubricant can be measured by washing the surface of the base layer with a solvent and analyzing the resulting washing liquid by electric field separation mass spectrometry.
[0063] The base layer 1 may have a surface treated with corona discharge. By subjecting the surface of the base layer 1 to the corona discharge treatment, the printing properties of the surface of the base layer 1 can be improved.
[0064] From the viewpoint of reducing the thickness of the battery packaging material 10 and forming the battery packaging material 10 with excellent shape stability after molding, the thickness of the base material layer 1 is preferably about 4 μm or more, more preferably about 10 μm or more and 75 μm or less, and further preferably about 10 μm or more and 50 μm or less.
[0065] In the battery packaging material of the present invention, from the viewpoint of improving moldability, the substrate layer 1 preferably includes a polyester film having a surface orientation degree as follows: when infrared absorption spectra in 18 directions from 0° to 170° at intervals of 10° are obtained using a total reflection method of Fourier transform infrared spectroscopy for the surface on the outermost layer side (the side opposite to the barrier layer 3), the following formula is satisfied (surface orientation degree: Y max / Y min ) has the following surface orientation degree: Y max / Y min .
[0066] Y max / Y min =1.4 or more and 2.7 or less
[0067] Y max The absorption peak intensity Y of the infrared absorption spectrum in the above 18 directions is 1340 Divided by the absorption peak intensity Y 1410 The maximum value obtained.
[0068] Y min The absorption peak intensity Y of the infrared absorption spectrum in the above 18 directions is 1340 Divided by the absorption peak intensity Y 1410 The minimum value obtained.
[0069] Maximum Y max and minimum value Y min In the calculation of 1340 / Y 1410 , select the maximum value Y from these max and minimum value Y min .
[0070] The specific measurement conditions of the infrared absorption spectrum are as follows. In addition, when measuring the infrared absorption spectrum of the surface of the polyester film, if the surface of the polyester film is exposed, it can be performed in a state where it is laminated on the battery packaging material. In addition, when the surface coating layer 6 described later is laminated on the surface of the polyester film, the surface coating layer 6 can be removed to form a state where the surface of the polyester film is exposed and the measurement is performed. For example, a polyester film is obtained from a battery packaging material having a polyester film and a polyamide film in sequence from the substrate layer to the barrier layer side. When the measurement is performed using the total reflection method of Fourier transform spectroscopy, the polyamide film can be peeled off the polyester film or dissolved, and the absorption peak intensity Y of the obtained polyester film can be measured. 1340 and the absorption peak intensity Y 1410 .
[0071] (Measurement conditions of infrared absorption spectrum)
[0072] Beam splitter (with single reflection ATR attachment)
[0073] Detector: MCT (Hg Cd Te)
[0074] Wave number resolution: 8cm-1
[0075] IRE: Ge
[0076] Angle of incidence: 30°
[0077] Polarizer: Wire grid, S polarized
[0078] Baseline: Average value of the intensity in the wave number range of 1800 cm-1 to 2000 cm-1
[0079] Absorption peak intensity Y 1340 : The value obtained by subtracting the baseline value from the maximum value of the peak intensity in the wave number range of 1335 cm-1 to 1342 cm-1
[0080] Absorption peak intensity Y 1410 : The value obtained by subtracting the baseline value from the maximum value of the peak intensity in the wave number range of 1400 cm-1 to 1410 cm-1
[0081] The infrared absorption spectra in 18 directions were obtained by placing a polyester film as a sample horizontally on a sample holder and rotating it together with the Ge crystal placed on the sample by 10 degrees at a time. The incident angle is the angle between the vertical line (normal line) and the incident light.
[0082] From the viewpoint of further improving the moldability of the battery packaging material, the surface orientation degree (Y max / Y min), more preferably 1.6 to 2.7, and even more preferably 1.6 to 2.4.
[0083] Having the surface orientation degree as described above: Y max / Y min The polyester film can be produced, for example, by appropriately adjusting the stretching method, stretching ratio, stretching speed, cooling temperature, heat setting temperature, etc. when producing the polyester film. In addition, a commercially available product can be used as the polyester film.
[0084] The polyester film is preferably composed of a biaxially stretched polyester film, particularly a biaxially stretched polyethylene terephthalate film.
[0085] The thickness of the polyester film is not particularly limited, but from the viewpoint of thinning the battery packaging material and exhibiting excellent moldability, it is preferably about 20 μm or less, more preferably about 1 μm to 15 μm, and more preferably about 3 μm to 12 μm.
[0086] [Adhesive layer 2]
[0087] In the battery packaging material of the present invention, the adhesive layer 2 is a layer provided between the base layer 1 and the barrier layer 3 in order to firmly adhere them.
[0088] The adhesive layer 2 is formed of an adhesive capable of bonding the substrate layer 1 to the barrier layer 3. The adhesive used in forming the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. In addition, there is no particular limitation on the bonding mechanism of the adhesive used in forming the adhesive layer 2, and it may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressing type, and the like.
[0089] Adhesive components that can be used in the formation of the adhesive layer 2 include, specifically, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolyesters; polycarbonate; polyether adhesives; polyurethane adhesives; epoxy resins; phenolic resins; polyamide resins such as nylon 6, nylon 66, nylon 12, and copolyamides; polyolefin resins such as polyolefins, carboxylic acid-modified polyolefins, and metal-modified polyolefins; polyvinyl acetate resins; cellulose adhesives; (meth) acrylic resins; polyimide resins; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components can be used alone or in combination of two or more. Among these adhesive components, polyurethane-based adhesives are preferably used.
[0090] The thickness of the adhesive layer 2 is not particularly limited as long as it functions as an adhesive layer, and can be, for example, about 1 μm to 10 μm, preferably about 2 μm to 5 μm.
[0091] [Barrier layer 3]
[0092] In the battery packaging material 10, the barrier layer 3 is a layer that has the function of preventing water vapor, oxygen, light, etc. from invading the interior of the battery in addition to improving the strength of the battery packaging material. The barrier layer 3 is preferably a metal layer, that is, a layer formed of metal. As the metal constituting the barrier layer 3, specifically, aluminum, stainless steel, titanium, etc. can be cited, and aluminum is preferably cited. The barrier layer 3 can be formed of a metal foil or a metal vapor-deposited film, an inorganic oxide vapor-deposited film, a carbon-containing inorganic oxide vapor-deposited film, a film provided with these vapor-deposited films, etc., and is preferably formed of a metal foil, and more preferably formed of an aluminum foil. When manufacturing a battery packaging material, from the viewpoint of preventing wrinkles or pinholes from being generated in the barrier layer 3, it is more preferable to form the barrier layer from a soft aluminum alloy foil such as annealed aluminum (JIS H4160: 1994 A8021H-O, JIS H4160: 1994 A8079H-O, JIS H4000: 2014 A8021P-O, JIS H4000: 2014 A8079P-O).
[0093] From the viewpoint of improving the formability of the barrier layer 3, the barrier layer 3 (especially when formed of an aluminum alloy foil) preferably has an average grain size of approximately 10.0 μm or less, preferably approximately 1.0 μm to 7.0 μm or less, and more preferably approximately 1.0 μm to 3.0 μm or less.
[0094] In the present invention, the average crystal grain size in the aluminum alloy foil layer refers to: when observing a cross section of the aluminum alloy foil layer in the thickness direction using a scanning electron microscope (SEM), for 100 aluminum alloy grains 31 located in the field of view, Figure 5 As shown in the schematic diagram of FIG. 1 , the maximum diameter x of each crystal grain is measured, and the maximum diameter x of 100 crystal grains is averaged to obtain the value. The maximum diameter x of each crystal grain is as follows: Figure 5 As shown in the schematic diagram, for the grains observed by SEM, the straight line distance between one epitaxial point of the grain and another epitaxial point of the same grain becomes the maximum diameter. The cross section in the thickness direction of the aluminum alloy foil layer observed by SEM is the cross section obtained by cutting the cross section with a plane perpendicular to the rolling direction. In addition, Figure 5 This is a schematic diagram, and therefore, the illustration is omitted, and 100 crystal grains 31 are not illustrated.
[0095] In the present invention, in a cross section in the thickness direction of the laminate constituting the battery packaging material, when the diameter y of each second phase particle is measured among any 100 second phase particles 32 in the field of view of the barrier layer 3 observed by an optical microscope, the average diameter y of the top 20 second phase particles in descending order of the diameter y is preferably about 5.0 μm or less, more preferably about 1.0 μm or more and about 4.0 μm or less, and further preferably about 1.0 μm or more and about 3.5 μm or less. The diameter y of each second phase particle is as follows: Figure 5 As shown in the schematic diagram, for particles observed by SEM, the straight line distance connecting one point of the epitaxy of the second phase particle and another point of the epitaxy of the same second phase particle becomes the maximum diameter. By making the average crystal grain size in the barrier layer 3 about 10.0 μm or less and making the above diameter of the second phase particle 32 within such a range, the moldability of the battery packaging material can be further improved. In addition, Figure 5 This is a schematic diagram, and therefore, the illustration is omitted, and 100 crystal grains 31 are not illustrated.
[0096] In the present invention, for example, when the barrier layer 3 is formed of an aluminum alloy, the second phase particles contained in the aluminum alloy form intermetallic compounds such as Al-(Fe·Mn)-Si. Such second phase particles mainly generated during solidification in the casting process cannot be completely fixed in the subsequent process and remain.
[0097] When observing the cross section of the barrier layer 3 in the thickness direction with a scanning electron microscope (SEM), the grains usually depict boundary lines connecting multiple crystals. In contrast, the second phase particles are usually crystals with a single boundary line. In addition, the phases of the grains and the second phase particles are different, so the colors are different on the SEM image, and the second phase particles are often observed as white. In addition, when observing the cross section of the barrier layer 3 in the thickness direction with an optical microscope, due to the difference in phases between the grains and the second phase particles, only the second phase particles are observed as black, so observation becomes easy.
[0098] When the barrier layer 3 is formed of an aluminum alloy, the composition of the aluminum alloy preferably contains 0.7 mass % to 2.5 mass % of Fe, 0.05 mass % to 0.30 mass % to 0.30 mass % of Si.
[0099] The thickness of the barrier layer 3 is not particularly limited as long as it functions as a barrier layer for water vapor, etc., and can be, for example, about 10 μm to 100 μm, preferably about 10 μm to 55 μm, and more preferably about 10 μm to 38 μm.
[0100] In addition, in order to stabilize adhesion, prevent dissolution or corrosion, etc., the barrier layer 3 preferably has a base film layer on at least one side, preferably both sides. The base film layer is a layer formed by subjecting the surface of the barrier layer to a chemical surface treatment, and the chemical surface treatment refers to a treatment for forming an acid-resistant film on the surface of the barrier layer. As chemical surface treatment, for example, there can be listed: chromate treatment using chromium compounds such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, dichromium phosphate, chromium acetoacetate, chromium chloride, potassium chromium sulfate; chromate phosphate treatment using phosphoric acid compounds such as sodium phosphate, potassium phosphate, ammonium phosphate, polyphosphoric acid; chromate treatment using an aminophenol polymer having repeating units represented by the following general formulas (1) to (4), etc. In addition, in the aminophenol polymer, the repeating units represented by the following general formulas (1) to (4) may contain a single type or any combination of two or more types.
[0101]
[0102] In the general formulae (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group or a benzyl group. 1 and R 2 are the same or different and represent hydroxyl, alkyl or hydroxyalkyl. 1 and R 2 Examples of the alkyl group represented by , include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl and other linear or branched alkyl groups having 1 to 4 carbon atoms. 1 and R 2 Examples of the hydroxyalkyl group include hydroxymethyl, 1-hydroxyethyl, 2-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 3-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 3-hydroxybutyl, 4-hydroxybutyl, and other linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group shown in the formula (1) to (4) may be the same or different. In the general formulas (1) to (4), X is preferably a hydrogen atom, a hydroxyl group or a hydroxyalkyl group. The number average molecular weight of the aminophenol polymer having the repeating unit shown in the general formula (1) to (4) is preferably 500 to 1,000,000, for example, and more preferably 1,000 to 20,000.
[0103] In addition, as a chemical surface treatment method for imparting corrosion resistance to the barrier layer 3, the following method can be cited: a method in which a substance obtained by dispersing fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, tin oxide, or barium sulfate in phosphoric acid is applied, and a baking treatment is performed at 150°C or above, thereby forming a corrosion-resistant base film layer on the surface of the barrier layer 3. In addition, a resin layer obtained by crosslinking a cationic polymer with a crosslinking agent can be further formed on the corrosion-resistant base film layer. Here, as a cationic polymer, for example, polyethyleneimine, an ionic polymer coordination compound formed by polyethyleneimine and a polymer having a carboxylic acid, a primary amine-grafted acrylic resin obtained by grafting a primary amine on an acrylic acid main skeleton, polyallylamine or its derivatives, aminophenol, etc. can be cited. As these cationic polymers, only one type can be used, or two or more types can be used in combination. In addition, as a crosslinking agent, for example, a compound having at least one functional group selected from an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, a silane coupling agent, etc. can be cited. As these cross-linking agents, only one type may be used, or two or more types may be used in combination.
[0104] Chemical surface treatment can be carried out by only one chemical surface treatment, or by combining two or more chemical surface treatments. In addition, these chemical surface treatments can be carried out by using one compound alone, or by combining two or more compounds. Among chemical surface treatments, preferably chromate treatment or chemical surface treatment combining chromium compounds, phosphoric acid compounds and aminophenol polymers, etc. Among chromium compounds, preferably chromic acid compounds.
[0105] There is no particular limitation on the amount of the base film layer formed on the surface of the barrier layer 3 in the chemical reaction surface treatment. For example, in the case of the above-mentioned chromate treatment, it is desirable to form a base film layer on the surface of the barrier layer 3 per m 2 The chromic acid compound is contained in the following proportions: 0.5 mg to 50 mg, preferably 1.0 mg to 40 mg, of the chromic acid compound in terms of chromium; 0.5 mg to 50 mg, preferably 1.0 mg to 40 mg, of the phosphorus compound in terms of phosphorus; and 1 mg to 200 mg, preferably 5.0 mg to 150 mg, of the aminophenol polymer.
[0106] The chemical surface treatment is performed by applying a solution containing a compound used in forming the base film layer to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, etc., and then heating the barrier layer so that the temperature thereof becomes about 70° C. to 200° C. In addition, before the chemical surface treatment is performed on the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, etc. In this way, the degreasing treatment can more efficiently perform the chemical surface treatment on the surface of the barrier layer.
[0107] [Thermal Fusible Resin Layer 4]
[0108] In the battery packaging material of the present invention, the heat-fusible resin layer 4 corresponds to the innermost layer and is a layer for sealing the battery element by heat-fusion bonding the heat-fusible resin layers to each other when assembling the battery.
[0109] The resin component used for the heat-fusible resin layer 4 is not particularly limited as long as it can be heat-fusible, and examples thereof include polyolefins, cyclic polyolefins, carboxylic acid-modified polyolefins, and carboxylic acid-modified cyclic polyolefins.
[0110] Specifically, the polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); terpolymers of ethylene-butene-propylene, etc. Among these polyolefins, polyethylene and polypropylene are preferably included.
[0111] The above-mentioned cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. As the olefin constituting the above-mentioned cyclic polyolefin, for example, ethylene, propylene, 4-methyl-1-pentene, butadiene, isoprene, etc. can be cited. In addition, as the cyclic monomer constituting the above-mentioned cyclic polyolefin, for example, cyclic olefins such as norbornene can be cited; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene can be cited. Among these polyolefins, cyclic olefins are preferably cited, and norbornene is further preferably cited. In addition, styrene can also be cited as a monomer.
[0112] The carboxylic acid-modified polyolefin is a polymer obtained by modifying the polyolefin with a carboxylic acid by block polymerization or graft polymerization. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, itaconic anhydride, and the like.
[0113] The carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or a polymer obtained by block polymerization or graft polymerization of an α,β-unsaturated carboxylic acid or its anhydride on a cyclic polyolefin. The cyclic polyolefin modified with carboxylic acid is the same as described above. In addition, the carboxylic acid used in the modification is the same as the carboxylic acid used in the modification of the polyolefin.
[0114] Among these resin components, preferably, carboxylic acid-modified polyolefin is used, and more preferably, carboxylic acid-modified polypropylene is used.
[0115] The heat-adhesive resin layer 4 may be formed of a single resin component or a blended polymer of two or more resin components. The heat-adhesive resin layer 4 may be formed of only one layer or two or more layers of the same or different resin components.
[0116] In addition, it is preferred that a lubricant is present on the surface of the heat-fusible resin layer 4. The amount of lubricant present on the surface of the heat-fusible resin layer 4 is not particularly limited as long as the above-mentioned total amount is satisfied. From the viewpoint of having further high moldability and forming a battery packaging material with excellent continuous productivity of the battery, 10 mg / m 2 More than 50 mg / m 2 The following are about 15 mg / m 2 Above 40 mg / m 2 The method for measuring the amount of lubricant present on the surface of the heat-fusible resin layer 4 is the same as the method for measuring the amount of lubricant present on the surface of the laminated body described above. The types of lubricant present on the surface of the heat-fusible resin layer 4 can be the lubricant exemplified in the above-mentioned base material layer 1.
[0117] As a method for setting the amount of lubricant present on the surface of the thermally-adhesive resin layer 4 to the above-mentioned amount, there can be listed a method of coating a lubricant on the surface of the thermally-adhesive resin layer 4; or a method of making a lubricant contain a lubricant in the resin constituting the thermally-adhesive resin layer 4 and heating it, thereby causing the lubricant to seep out on the surface.
[0118] The thickness of the thermally fusible resin layer 4 is not particularly limited as long as it can function as a thermally fusible resin layer, but is preferably about 60 μm or less, and more preferably about 15 μm to 40 μm or less.
[0119] [Adhesive layer 5]
[0120] In the battery packaging material of the present invention, the adhesive layer 5 is a layer provided between the barrier layer 3 and the heat-fusible resin layer 4 as necessary in order to firmly adhere them.
[0121] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-fusible resin layer 4. As the resin used for forming the adhesive layer 5, the same resin as the adhesive exemplified in the adhesive layer 2 can be used in terms of bonding mechanism, type of adhesive component, etc. In addition, as the resin used for forming the adhesive layer 5, polyolefin-based resins such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin exemplified in the above-mentioned heat-fusible resin layer 4 can also be used. From the viewpoint of excellent adhesion between the barrier layer 3 and the heat-fusible resin layer 4, as the polyolefin, carboxylic acid-modified polyolefin is preferred, and carboxylic acid-modified polypropylene is particularly preferred.
[0122] In addition, from the viewpoint of reducing the thickness of the battery packaging material and making it a battery packaging material with excellent shape stability after molding, the adhesive layer 5 may be a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the same carboxylic acid-modified polyolefin and carboxylic acid-modified cyclic polyolefin as exemplified in the thermally fusible resin layer 4 can be preferably exemplified.
[0123] The curing agent is not particularly limited as long as it can cure the acid-modified polyolefin. Examples of the curing agent include epoxy curing agents, polyfunctional isocyanate curing agents, carbodiimide curing agents, and oxazoline curing agents.
[0124] The epoxy curing agent is not particularly limited as long as it is a compound having at least one epoxy group. Examples of the epoxy curing agent include epoxy resins such as bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, and polyglycerol polyglycidyl ether.
[0125] The polyfunctional isocyanate curing agent is not particularly limited as long as it is a compound with more than 2 isocyanate groups. As a specific example of the polyfunctional isocyanate curing agent, isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), the product obtained by polymerizing or uric acid esterification thereof, their mixture or copolymers with other polymers etc. can be listed.
[0126] The carbodiimide curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). The carbodiimide curing agent is preferably a polycarbodiimide compound having at least two carbodiimide groups.
[0127] The oxazoline curing agent is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the oxazoline curing agent include the Epocros series manufactured by Nippon Shokubai Co., Ltd. and the like.
[0128] From the viewpoint of improving the adhesion between the barrier layer 3 and the thermally-adhesive resin layer 4 through the adhesive layer 5 , etc., the curing agent may be composed of two or more compounds.
[0129] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of 0.1 mass % to 50 mass %, more preferably in the range of 0.1 mass % to 30 mass %, and further preferably in the range of 0.1 mass % to 10 mass %.
[0130] The thickness of the adhesive layer 5 is not particularly limited as long as it functions as an adhesive layer. When the adhesive exemplified in the adhesive layer 2 is used, it is preferably about 2 μm or more and about 10 μm or less, and more preferably about 2 μm or more and about 5 μm or less. In addition, when the resin exemplified in the hot-melt resin layer 4 is used, it is preferably about 2 μm or more and about 50 μm or less, and more preferably about 10 μm or more and about 40 μm or less. In addition, when it is a cured product of an acid-modified polyolefin and a curing agent, it is preferably about 30 μm or less, and more preferably about 0.1 μm or more and about 20 μm or less, and further preferably about 0.5 μm or more and about 5 μm or less. In addition, when the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating, etc.
[0131] [Surface coating layer 6]
[0132] In the battery packaging material 10 of the present invention, for the purpose of improving design, electrolyte resistance, friction resistance, moldability, etc., a surface coating layer 6 may be provided on the substrate layer 1 (the side of the substrate layer 1 opposite to the barrier layer 3) as required. The surface coating layer 6 is a layer located at the outermost layer when the battery is assembled. When the surface coating layer 6 is provided, a lubricant is present on the surface of the surface coating layer 6 of the battery packaging material (i.e., the surface on the substrate layer 1 side mentioned above).
[0133] The surface coating layer 6 can be formed by polyvinylidene chloride, polyester resin, polyurethane resin, acrylic resin, epoxy resin, etc., for example. In addition, from the viewpoint of further improving the electrolyte resistance of the surface of the battery packaging material, the surface coating layer 6 can be formed by a mixed resin of a combination of polyurethane resin and acrylic resin, etc. Among these, the surface coating layer 6 is preferably formed by a two-liquid curing resin. As the two-liquid curing resin forming the surface coating layer, for example, two-liquid curing polyurethane resin, two-liquid curing polyester resin, two-liquid curing epoxy resin, etc. can be listed. In addition, additives can also be added to the surface coating layer.
[0134] As additives, for example, particles with a particle size of about 0.5 nm or more and about 5 μm or less can be listed. There is no particular restriction on the material of the additive, for example, metals, metal oxides, inorganic substances, organic substances, etc. can be listed. In addition, there is no particular restriction on the shape of the additive, for example, spherical, fibrous, plate-like, amorphous, hollow spherical, etc. can be listed. As additives, specifically, talc, silicon dioxide, graphite, kaolin, montmorillonite, montmorillonite, synthetic mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, aluminum oxide, carbon black, carbon nanotubes, high melting point nylon, cross-linked acrylic acid, cross-linked styrene, cross-linked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. These additives can be used alone or in combination of two or more. Among these additives, silicon dioxide, barium sulfate, and titanium oxide are preferably used from the viewpoint of dispersion stability and cost, etc. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment in advance.
[0135] The method for forming the surface coating layer 6 is not particularly limited, and one example is a method of coating a two-component curing resin forming the surface coating layer 6 on one surface of the base layer 1. When an additive is added, the additive may be added to the two-component curing resin, mixed, and then coated.
[0136] The content of the additive in the surface coating layer 6 is not particularly limited, but is preferably about 0.05 mass % to about 1.0 mass %, and more preferably about 0.1 mass % to about 0.5 mass %.
[0137] The thickness of the surface coating layer 6 is not particularly limited as long as the above-mentioned function as the surface coating layer 6 is exerted and the battery packaging material satisfies the above-mentioned physical properties. For example, it can be about 0.5 μm to about 10 μm, preferably about 1 μm to about 5 μm.
[0138] 3. Method for manufacturing battery packaging material
[0139] The method for producing the battery packaging material of the present invention is not particularly limited as long as a laminated body in which layers of a predetermined composition are laminated can be obtained, and includes a step of laminating at least a substrate layer 1, a barrier layer 3, and a heat-fusible resin layer 4 in this order to obtain a laminated body. As a method for making a lubricant present on the surface on the substrate layer 1 side, a lubricant may be applied to the surface on the substrate layer 1 side, or a lubricant may be contained in the resin constituting the layer on the substrate layer 1 side (for example, the substrate layer 1 or the surface coating layer 6) so that the lubricant seeps out on the surface on the substrate layer 1 side. Similarly, a lubricant may be applied to the surface of the heat-fusible resin layer 4, or a lubricant may be contained in the resin constituting the heat-fusible resin layer 4 so that the lubricant seeps out on the surface of the heat-fusible resin layer 4.
[0140] An example of a method for producing a battery packaging material of the present invention is as follows. First, a laminated body (hereinafter sometimes referred to as "laminated body A") is formed by laminating a substrate layer 1, an adhesive layer 2, and a barrier layer 3 in this order. Specifically, the formation of the laminated body A can be performed by the following dry lamination method, in which an adhesive for forming the adhesive layer 2 is applied to the substrate layer 1 or the barrier layer 3 whose surface has been chemically treated as required by a coating method such as a gravure coating method or a roll coating method, and after drying, the barrier layer 3 or the substrate layer 1 is laminated, and the adhesive layer 2 is cured.
[0141] Next, the heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is laminated directly on the barrier layer 3, the resin component constituting the heat-fusible resin layer 4 can be coated on the barrier layer 3 of the laminate A by a gravure coating method, a roll coating method, or the like. In addition, when an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4, for example, the following methods can be cited: (1) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 on the barrier layer 3 of the laminate A by co-extrusion (co-extrusion lamination method); (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-fusible resin layer 4 are laminated, and laminating the laminate on the barrier layer 3 of the laminate A by a heat lamination method; (3) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 on the barrier layer 3 of the laminate A by co-extrusion lamination method; , a method in which an adhesive for forming an adhesive layer 5 is laminated by an extrusion method or a solution coating method, and then dried at a high temperature and then baked, and a hot-melt adhesive resin layer 4 pre-filmed into a film is laminated on the adhesive layer 5 by a heat lamination method; (4) a method in which the molten adhesive layer 5 is poured between the barrier layer 3 of the laminate A and the hot-melt adhesive resin layer 4 pre-filmed into a sheet, and the laminate A and the hot-melt adhesive resin layer 4 are bonded together via the adhesive layer 5 (sandwich lamination method), etc.
[0142] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the substrate layer 1 on the opposite side to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the substrate layer 1. In addition, the order of the step of laminating the barrier layer 3 on the surface of the substrate layer 1 and the step of laminating the surface coating layer 6 on the surface of the substrate layer 1 is not particularly limited. For example, after the surface coating layer 6 is formed on the surface of the substrate layer 1, the barrier layer 3 can be formed on the surface of the substrate layer 1 on the opposite side to the surface coating layer 6.
[0143] As described above, a laminated body including a surface coating layer 6 provided as required / a substrate layer 1 / an adhesive layer 2 provided as required / a barrier layer 3 with a chemically treated surface provided as required / an adhesive layer 5 provided as required / a heat-fusible resin layer 4 is formed. In order to strengthen the adhesiveness of the adhesive layer 2 or the adhesive layer 5 provided as required, a heat treatment such as a hot roll contact type, a hot air type, a near infrared type, or a far infrared type may be applied. As the conditions for such a heat treatment, for example, a temperature of 150° C. to 250° C. inclusive for 1 to 5 minutes may be cited.
[0144] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to surface activation treatment such as corona discharge treatment, sandblasting, oxidation treatment, ozone treatment, etc., as required, in order to improve or stabilize the film forming properties, lamination processing, and adaptability to secondary processing of the final product (packaging, embossing molding). For example, by subjecting at least one surface of the substrate layer to corona discharge treatment, the film forming properties, lamination processing, and adaptability to secondary processing of the final product can be improved or stabilized. In addition, for example, by subjecting the substrate layer 1 to corona discharge treatment on the surface opposite to the barrier layer 3, the printing adaptability of the ink on the surface of the substrate layer 1 can be improved.
[0145] 4. Application of battery packaging materials
[0146] The battery packaging material of the present invention is used in a packaging body for sealing and storing battery components such as a positive electrode, a negative electrode, and an electrolyte. That is, a battery component including at least a positive electrode, a negative electrode, and an electrolyte can be stored in a packaging body formed by the battery packaging material of the present invention to prepare a battery.
[0147] Specifically, a battery element including at least a positive electrode, a negative electrode and an electrolyte is wrapped with the battery packaging material of the present invention in a state where the metal terminals connected to the positive electrode and the negative electrode protrude to the outside, so that a flange portion (an area where the heat-fusible resin layers are in contact with each other) can be formed at the periphery of the battery element, and the heat-fusible resin layers of the flange portion are heat-sealed to each other to seal, thereby providing a battery using the battery packaging material. In addition, when the battery element is accommodated in a packaging body formed by the battery packaging material of the present invention, the packaging body is formed in a manner such that the heat-fusible resin portion of the battery packaging material of the present invention is on the inside (the surface in contact with the battery element).
[0148] The battery packaging material of the present invention can be used in any type of primary battery or secondary battery, preferably a secondary battery. There is no particular restriction on the type of secondary battery to which the battery packaging material of the present invention is applicable, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, multivalent cation batteries, capacitors, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be cited as suitable application objects of the battery packaging material of the present invention.
[0149] Example
[0150] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0151] (Example 1-29 and Comparative Example 1-14)
[0152] <Manufacturing of battery packaging materials>
[0153] An aluminum alloy foil (35 μm thick) is laminated as a barrier layer on a substrate layer formed of the resin in Table 1 by dry lamination. Specifically, a two-liquid polyurethane adhesive (polyol compound and aromatic isocyanate compound) is coated on one side of the aluminum alloy foil to form an adhesive layer (3 μm thick) on the aluminum alloy foil. Next, the adhesive layer and the substrate layer on the barrier layer are laminated by dry lamination, and then subjected to an aging treatment at 40°C for 24 hours to produce a laminate of substrate layer / adhesive layer / barrier layer. In addition, a chemical surface treatment is applied to both sides of the aluminum alloy foil. The chemical surface treatment of the aluminum alloy foil is performed as follows: a treatment solution comprising a phenolic resin, a chromium fluoride compound and phosphoric acid is added at a chromium coating amount of 10 mg / m 2(dry mass), applied to both sides of the aluminum foil by a roll coating method, and baked for 20 seconds under the condition that the film temperature is 180°C or higher. Next, on the barrier layer of the laminate, a 20 μm carboxylic acid-modified polypropylene (disposed on the barrier layer side) and a 15 μm random polypropylene (innermost layer side) were co-extruded, and an adhesive layer and a heat-fusible resin layer were laminated on the barrier layer to obtain a battery packaging material having a substrate layer / adhesive layer / barrier layer / adhesive layer / heat-fusible resin layer laminated in this order.
[0154] In Examples 1-7 and 9-29, the lubricant present on the surface of the battery packaging material is a lubricant (erucic acid amide) mixed with the resin constituting the base material layer and the heat-fusible resin layer and heated for a certain period of time after the battery packaging material is manufactured to make it seep out. On the other hand, the lubricant of Example 8 is a lubricant (erucic acid amide) applied to the surface of the base material layer and the heat-fusible resin layer after the battery packaging material is manufactured.
[0155] In addition, as the aluminum alloy foil, in Examples 1-21, 23-28 and Comparative Examples 1-14, the aluminum alloy foil having the average crystal grain size of 10 μm or less and the diameter of the second phase particles of 3 μm or less was used, and in Example 22, the aluminum alloy foil having the average crystal grain size of more than 10 μm and the diameter of the second phase particles of 3 μm or less was used. In addition, in Example 29, the aluminum alloy foil having the average crystal grain size of 10 μm or less and the diameter of the second phase particles of 6 μm was used.
[0156] The average crystal grain size and the second phase particles of the aluminum alloy foil were measured by the following methods.
[0157] <Measurement of Average Grain Size of Aluminum Alloy Foil>
[0158] The average crystal grain size of the aluminum alloy foil used as the aluminum alloy foil layer of the embodiment and the comparative example is obtained by observing the cross section of the aluminum alloy foil layer in the thickness direction with a scanning electron microscope (product name S-4800 manufactured by Hitachi High-Tech Corporation), randomly selecting 100 aluminum alloy grains located in the field of view, measuring the maximum diameter x of each grain, and taking the average of the maximum diameter x of the 100 grains. The maximum diameter x of each grain refers to the diameter of the grain observed with the SEM, where the straight-line distance between one point of the epitaxial extension of the grain and another point of the epitaxial extension of the same grain becomes the maximum.
[0159] <Measurement of Second Phase Particle Diameter of Aluminum Alloy Foil>
[0160] The diameter of the second phase particles of the aluminum alloy foil used as the aluminum alloy foil layer of the embodiment and the comparative example was determined by observing the cross section in the thickness direction with an optical microscope (product name CX31-P manufactured by OLYMPUS Corporation), randomly selecting 100 second phase particles in the field of view, and calculating the average value of the diameter y of each second phase particle. The diameter y of each second phase particle refers to the diameter at which the straight line distance connecting one point of the epitaxial extension of the second phase particle and another point of the epitaxial extension of the same second phase particle becomes the maximum for the particle observed with the SEM.
[0161] (Determination of slip dosage)
[0162] Each battery packaging material obtained above was cut into A4 size to prepare a sample. Next, the substrate layer side surface and the heat-fusible resin layer surface of each sample were cleaned with 30 ml of methanol, and the recovered methanol was volatilized and dried in a nitrogen stream to obtain a solid. Next, 1.5 ml of methanol was added to the solid to redissolve the solid, and a gas chromatograph mass spectrometer (GCMS, QP2010 manufactured by Shimadzu Corporation, ionization method: electron impact ionization method (EI method), detector: quadrupole detector, column: Inert Cap 5MS) was used to measure the amount of lubricant on the substrate layer side surface and the heat-fusible resin layer surface. As a result, the amount of lubricant on the surface of each battery packaging material was the value shown in Table 1.
[0163] <Measurement of surface orientation>
[0164] For the surface of the polyethylene terephthalate (PET) film used as the substrate layer in Examples 11-15 and 23-28 (the surface on the opposite side to the barrier layer), an infrared absorption spectrum was obtained in 18 directions from 0° to 170° at intervals of 10° using the total reflection method (ATR) of Fourier transform infrared spectroscopy (FT-IR), and the absorption peak intensity Y of the infrared absorption spectrum in 18 directions was calculated. 1340 (CH2 pitch vibration) and from the absorption peak intensity Y 1410 The values of (C=C stretching vibration) are calculated for Y 1340 / Y 1410 , from these the maximum value Y max and minimum value Y min Calculate surface orientation: Y max / Y min .
[0165] The results are shown in Table 1. In Examples 11 to 16, Y max =2.1, Y min is 1.3, surface orientation degree: Y max / Y min In Example 23, Y max 2.21, Ymin is 1.13, surface orientation degree: Y max / Y min is 1.96. In Example 24, Y max 2.14, Y min is 1.08, surface orientation degree: Y max / Y min In Example 25, Y max 2.16, Y min is 1.18, surface orientation degree: Y max / Y min In Example 26, Y max 1.99, Y min is 1.28, surface orientation degree: Y max / Y min In Example 27, Y max =2.15, Y min is 1.14, surface orientation degree: Y max / Y min In Example 28, Y max 2.22, Y min is 1.06, surface orientation degree: Y max / Y min It is 2.09.
[0166] (Measurement conditions of infrared absorption spectrum)
[0167] Spectrometer: Nicoleti S10 FT-IR manufactured by Thermo Fisher Scientific
[0168] Attachment: 1-reflection ATR attachment (Seagull)
[0169] Detector: MCT (HgCdTe)
[0170] Wave number resolution: 8cm-1
[0171] IRE: Ge
[0172] Angle of incidence: 30°
[0173] Polarizer: Wire grid, S polarized
[0174] Baseline: Average value of the intensity in the wave number range of 1800 cm-1 to 2000 cm-1
[0175] Absorption peak intensity Y 1340 : The value obtained by subtracting the baseline value from the maximum value of the peak intensity in the wave number range of 1335 cm-1 to 1342 cm-1
[0176] Absorption peak intensity Y 1410 : The value obtained by subtracting the baseline value from the maximum value of the peak intensity in the wave number range of 1400 cm-1 to 1410 cm-1
[0177] The infrared absorption spectra in 18 directions were obtained by placing a polyester film as a sample horizontally on a sample holder and rotating the Ge crystal placed on the sample by 10 degrees at a time. The incident angle is the angle between the vertical line (normal line) and the incident light.
[0178] (Moldability Evaluation)
[0179] Each battery packaging material obtained above was cut into a rectangular shape of 80 mm×120 mm to prepare samples. These samples were molded using a molding die having a diameter of 30 mm×50 mm (female mold, surface of the surface roughness standard sheet for comparison specified in Table 2 of JIS B 0659-1: 2002 Appendix 1 (reference), with a maximum height roughness (Rz nominal value) of 3.2 μm) and a corresponding molding die (male mold, surface of the surface roughness standard sheet for comparison specified in Table 2 of JIS B 0659-1: 2002 Appendix 1 (reference), with a maximum height roughness (Rz nominal value) of 1.6 μm) at a pressing pressure of 0.4 MPa, with the molding depth increasing by 0.5 mm from a molding depth of 0.5 mm, and a molding depth 0.5 mm shallower than the molding depth when pinholes were generated in the battery packaging material was set as the critical molding depth of the sample. Based on the critical molding depth, the moldability of the battery packaging material was evaluated based on the following criteria.
[0180] A: The limit molding depth is 6.0mm or more
[0181] B: The limit molding depth is 5.0 mm or more and 5.5 mm or less
[0182] C: The limit molding depth is 4.0 mm or more and 4.5 mm or less
[0183] D: The limit molding depth is less than 3.5mm
[0184] (Evaluation of continuous productivity of batteries)
[0185] Each battery packaging material obtained in the above was cut into a rectangular shape of 80 mm × 120 mm to prepare a sample. Then, these samples were cold-formed 1000 times each at a pressing pressure of 0.4 MPa and a forming depth of 5 mm using a forming die (female die, surface of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1: 2002, Table 2, and the maximum height roughness (Rz nominal value) of 3.2 μm) and a corresponding forming die (male die, surface of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B0659-1: 2002, Table 2, and the maximum height roughness (Rz nominal value) of 1.6 μm) under an environment of temperature 24°C and relative humidity 50%. Then, the corners of the mold after cold forming were visually observed, and the continuous formability of the battery packaging material was evaluated based on the following criteria.
[0186] A: The lubricant does not transfer to the male and female molds, and the mold does not whiten, so continuous molding is high
[0187] B: The lubricant is transferred to only one of the male and female molds, and the mold is slightly whitened, so the continuous moldability is slightly higher
[0188] C: The lubricant was transferred to both the male and female molds, and the mold was whitened, so the continuous molding property was low (evaluation of printing property)
[0189] The surface of the substrate layer of each battery packaging material obtained above is printed with a pattern by pad printing. The pad printer used is SPACE PAD 6GX manufactured by Mishima Co., Ltd., and the ink used is UV ink PJU-A black manufactured by Navitas Co., Ltd. In addition, the ink is cured by irradiating UV with a wavelength of 254 nm from a distance of 10 cm for 30 seconds using Handy UV Lamp SUV-4 manufactured by AS-1. The cured printed surface is observed with an optical microscope and evaluated according to the following criteria. The results are shown in Table 1. In addition, the printing evaluation was performed in an environment of 24°C and a relative humidity of 50%.
[0190] 5: There is no missing print within the visible range
[0191] 4: The missing printing accounts for less than 2.5% of the total printed pattern
[0192] 3: The missing printing accounts for more than 2.5% and less than 5% of the whole printed pattern
[0193] 2: The missing printing accounts for more than 5% and less than 10% of the total printing pattern
[0194] 1: The missing printing accounts for more than 10% of the whole printing pattern
[0195] (Evaluation of tape removability)
[0196] The surface of the substrate layer of each battery packaging material obtained above is subjected to pad printing in the same manner as the evaluation of the printability described above. Scotch Tape #600 manufactured by 3M is pasted to the cured printed surface using a 200 g rubber roller in one reciprocating motion. Next, the pasted tape is peeled off at a peeling angle of 90°. The surface of the substrate layer (printed surface) of the portion where the tape was peeled off is observed under an optical microscope, and the range that can be visually confirmed is evaluated based on the following criteria. The results are shown in Table 1. In addition, the evaluation of the tape peelability is carried out in an environment of 24°C and a relative humidity of 50%.
[0197] 5: No peeling of printing
[0198] 4: Printing peeling accounts for more than 0% and less than 25% of the entire printed pattern
[0199] 3: Printing peeling accounts for more than 25% and less than 50% of the entire printed pattern
[0200] 2: Printing peeling accounts for more than 50% and less than 75% of the entire printed pattern
[0201] 1: Printing peeling accounts for more than 75% of the entire printed pattern
[0202] [Table 1]
[0203]
[0204] In Table 1, in Examples 6 and 11 and Comparative Examples 5 and 11, the surface of the substrate layer was subjected to a corona discharge treatment (marked with * in Table 1). In Examples 7 and 14 and Comparative Examples 6 and 12, the surface of the substrate layer was subjected to an easy-adhesion treatment (marked with ** in Table 1). The easy-adhesion treatment was performed using a coating liquid to which an acrylic resin and an isocyanate crosslinking agent were added. ONy is biaxially stretched nylon, PET is biaxially stretched polyethylene terephthalate, and PET / ONy is a laminated film obtained by dry lamination of polyethylene terephthalate (12 μm) and nylon (15 μm) with PET located on the side opposite to the barrier layer. In addition, PET·ONy is a case where the substrate layer is formed by a laminated film (HEPTAX HBN (general grade) manufactured by GUNZE CO., LTD.) obtained by coextrusion of polyethylene terephthalate (3 μm) and nylon (12 μm). In addition, PP refers to biaxially stretched polypropylene, PE refers to biaxially stretched polyethylene, and CPP refers to unstretched polypropylene.
[0205] As shown in Table 1, the lubricant was present on the surface of the substrate layer, and the total amount of the lubricant present on the surface of the substrate layer of the laminate and the lubricant present on the surface of the thermally fusible resin layer of the laminate was 15 mg / m 2 Above 60 mg / m 2 The battery packaging materials of Examples 1 to 29 below have high moldability and are excellent in continuous productivity of batteries.
Claims
1. A battery packaging material, characterized in that: The invention is composed of a laminated body having at least a base material layer, a barrier layer and a heat-fusible resin layer in this order, The base material layer includes at least one of a layer formed of polyester and a layer formed of polyamide, The heat-fusible resin layer includes a layer formed of polyolefin, The amount of lubricant present on the surface of the substrate layer side of the laminate is 3 mg / m 2 Above, 15mg / m 2 The amount of lubricant present on the surface of the heat-fusible resin layer of the laminate is 35 mg / m 2 Above, 50mg / m 2 Hereinafter, the total amount of the lubricant on the surface of the substrate layer side of the laminate and the lubricant on the surface of the thermally fusible resin layer of the laminate is 42 mg / m 2 Above, 60mg / m 2 In the following embodiment, a lubricant seeps out on the surface of the substrate layer side of the laminate and on the surface of the thermally fusible resin layer, The average crystal grain size of the barrier layer is less than 10 μm. In a cross section in the thickness direction of the laminate constituting the battery packaging material, when a diameter y of each second phase particle is measured among any 100 second phase particles within the field of view of the barrier layer observed using an optical microscope, the average diameter y of the top 20 second phase particles ranked in descending order of the diameter y is less than 3.0 μm.
2. The battery packaging material according to claim 1, wherein: The lubricant on the surface of the substrate layer side is formed of two or more lubricants.
3. The battery packaging material according to claim 1 or 2, characterized in that: The lubricant on the surface of the thermally adhesive resin layer is formed of two or more types of lubricants.
4. The battery packaging material according to claim 1 or 2, characterized in that: The thermally adhesive resin layer is formed of two or more layers of the same or different resin components.
5. The battery packaging material according to claim 1 or 2, characterized in that: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The adhesive layer and the heat-fusible resin layer are a co-extruded laminate.
6. The battery packaging material according to claim 1 or 2, characterized in that: An adhesive layer is provided between the barrier layer and the heat-fusible resin layer, The heat-fusible resin layer is formed of two or more layers of the same or different resin components. The adhesive layer and the heat-fusible resin layer are a co-extruded laminate.
7. The battery packaging material according to claim 1 or 2, characterized in that: The barrier layer has a thickness of 10 μm to 100 μm.
8. The battery packaging material according to claim 1 or 2, characterized in that: The barrier layer has a thickness of 10 μm to 55 μm.
9. The battery packaging material according to claim 1 or 2, characterized in that: The thickness of the barrier layer is greater than 55 μm and less than 100 μm.
10. The battery packaging material according to claim 1 or 2, characterized in that: The base material layer is a laminate including a layer formed of polyester and a layer formed of polyamide.
11. The battery packaging material according to claim 1 or 2, characterized in that: The substrate layer has a surface coating layer on the side opposite to the barrier layer.
12. The battery packaging material according to claim 1 or 2, characterized in that: The lubricant includes an amide lubricant.
13. The battery packaging material according to claim 1 or 2, wherein: The barrier layer has a base film layer on at least one surface thereof.
14. The battery packaging material according to claim 1 or 2, wherein: It is a packaging material for secondary batteries.
15. A battery, characterized in that: A battery element including at least a positive electrode, a negative electrode, and an electrolyte is accommodated in a packaging body formed of the battery packaging material according to any one of claims 1 to 14.
16. A method for manufacturing a battery packaging material, characterized in that: The method comprises the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in sequence to obtain a laminate. The base material layer includes at least one of a layer formed of polyester and a layer formed of polyamide, The heat-fusible resin layer includes a layer formed of polyolefin, The amount of lubricant present on the surface of the substrate layer side of the laminate is 3 mg / m 2 Above, 15mg / m 2 The amount of lubricant present on the surface of the heat-fusible resin layer of the laminate is 35 mg / m 2 Above, 50mg / m 2 Hereinafter, the total amount of the lubricant on the surface of the substrate layer side of the laminate and the lubricant on the surface of the thermally fusible resin layer of the laminate is 42 mg / m 2 Above, 60mg / m 2 The lubricant that seeps out is present on the surface of the substrate layer side of the laminate and on the surface of the thermally fusible resin layer in the following manner: The average crystal grain size of the barrier layer is 10 μm or less. In a cross section in the thickness direction of the laminate constituting the battery packaging material, when a diameter y of each second phase particle is measured among any 100 second phase particles within the field of view of the barrier layer observed using an optical microscope, the average diameter y of the top 20 second phase particles ranked in descending order of the diameter y is less than 3.0 μm.
17. The method for producing a battery packaging material according to claim 16, wherein: An adhesive layer is laminated between the barrier layer and the heat-fusible resin layer, The adhesive layer and the heat-fusible resin layer are laminated by co-extrusion.
18. The method for producing a battery packaging material according to claim 16, wherein: A step of laminating a laminate A, wherein the laminate A has an adhesive layer between the substrate layer and the barrier layer, and the substrate layer, the adhesive layer and the barrier layer are laminated in this order, The laminate A and the heat-fusible resin layer are laminated via a molten adhesive layer.
19. The method for producing a battery packaging material according to any one of claims 16 to 18, wherein: The method further includes subjecting at least one surface of the substrate layer to a corona discharge treatment.
Citation Information
Patent Citations
Layered package material, outer package material for battery, and the battery
JP2008287971A
Molding packaging material
CN104340514A
Battery packaging material
CN104969378A
Battery packaging material, method for manufacturing same, and battery
CN108886115A
Aluminum foil and its manufacture
JP1991120332A